From Abbild to Bild? Depiction and Resemblance in Husserl’s Phenomenology - Claudio Rozzoni (Aisthesis, 2017)
In a well-known course he gave in 1904-1905, Edmund Husserl developed a ‘threefold’ notion of image revolving around the notion of depiction [Abbildung]. More specifically, the phenomenological description allows a seeing-in to emerge as an essential characteristic of the image consciousness, in which an image object assumes the role of a representant [Repräsentant] in order to allow us to see the image subject in the image itself (thanks to “moments of resemblance” shared by image object and image subject). Nevertheless, our paper – focusing particularly on what might be called the depictive art par excellence, that is the portrait – aims to show that it would be erroneous to read the Husserlian notion of image exclusively on the basis of this earlier course: things seem to change significantly when Husserl develops a different notion of phantasy, and artistic images, in particular, are not to be thought of as resembling something else, but rather as expressive images producing their own model.